ADOPSI QRIS OLEH PEDAGANG TERAS MALIOBORO 1: ANALISIS KUALITAS LAYANAN DAN KEMUDAHAN PENGGUNAAN - Nadhif Firjatullah, Avilla; Wahyu Hidayat Riyanto; Dimas Bagus Wiranatakusuma (Universitas Muhammadiyah Bengkulu, 2025)
This study aims to study how service quality and ease of use impact the behavior of Teras Malioboro 1 merchants who switch from cash payments to QRIS. The increasing adoption of digital payment systems in Indonesia has made QRIS the main choice for street vendors to facilitate non-cash transactions. The quantitative method used in this study through a survey involving 275 merchants as respondents. The Structural Equation Modeling Partial Least Squares (SEM-PLS) method was used to analyze the data after being collected through a questionnaire. The results showed that the tendency of merchants to switch to QRIS was significantly influenced by ease of use, while service quality had an effect, but not directly. This indicates that the ease of using QRIS is more encouraging for merchants to switch from cash to digital payments than service quality. Thus, to increase QRIS adoption, primary attention should be paid to simplifying the interface and accessibility for merchants. This study contributes to the development of technology adoption strategies in the MSME sector and can assist policy makers in encouraging financial inclusion through the use of digital payment systems